Group dynamics as an intervention for Filipinos diagnosed with Tourette syndrome - Victorino, Maria Rowena Balmores (2008)
This study is about the Tourette Syndrome, a neurological disorder characterized by neurological tics that are often physical and verbal such as unusual blinking of the eye, peculiar hand movements, sound repititions and word echoing, among others. The study is a quasi-experimental research with a one-group-pretest-posttest design. It involved 5 Filipino male respondents suffering from Tourette Syndrome, all in the prime of their lives, age ranging from 19 to 28. Different counseling needs were discovered such as health concerns, anxiety for not finishing their studies, wariness about their future employment, inability to perform household and social responsibilities and concern over non acceptance by peers. This study validated the findings of earlier studies that group counseling is an effective intervention strategy to alleviate the condition of individuals suffering from Tourette Syndrome.